Clinical profile of autoimmune pancreatitis and its histological subtypes: an international multicenter survey - Kamisawa, Terumi; Werner, Jens; Bergmann, Frank (Pancreas, 2011)
Objective: The objective of this study was to clarify the clinical and pathophysiological characteristics of autoimmune pancreatitis (AIP) and its subtypes (lymphoplasmacytic sclerosing pancreatitis [LPSP] and idiopathic duct-centric pancreatitis [IDCP]) seen around the world. - Methods: An international multicenter survey of AIP was conducted in 15 institutes from 8 countries. We compared clinical and pathologic profiles of AIP (n = 731) and the clinical profiles of LPSP (n = 204) and IDCP (n = 64) patients. - Results: Patients with LPSP were approximately 16 years older than IDCP patients. Obstructive jaundice was a more frequent presentation in LPSP versus IDCP (75% vs 47%, P < 0.001), whereas abdominal pain (41% vs 68%, P < 0.001) and acute pancreatitis (5% vs 34%, P < 0.001) were more frequent in IDCP patients. Patients with LPSP were more likely to have diffuse swelling of the pancreas (40% vs 25%, P = 0.037) and elevated serum IgG4 levels (63% vs 23%, P < 0.001) but less likely to be associated with ulcerative colitis (1% vs 16%, P < 0.001). Clinical profiles of non-histologically confirmed AIP from Asia, the United States, and United Kingdom corresponded with that of LPSP, whereas those from Italy and Germany suggested a mixture of LPSP and IDCP. - Conclusions: Autoimmune pancreatitis is seen all around the world, with regional differences in the pathologic and clinical features. Lymphoplasmacytic sclerosing pancreatitis and IDCP have distinct clinical profiles.